Discourses on writing in the early modern Ottoman biographical dictionaries of calligraphers - Özakay, Damla. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2015., 2015)
This thesis examines three Ottoman biographical dictionaries of calligraphers written between the end of the sixteenth and the first half of the eighteenth century: Mustafa ‘Âli's Menâkıb-ı Hünerverân (d. 1600), Nefeszâde İbrahim’s (d. 1650-51) Gülzâr-ı Savâb and Suyolcuzâde Mehmed Necib’s (d. 1758) Devhatü’l-Küttâb. By considering the diversity of the representations of the act of writing and the figure of calligrapher in the texts the problems and limitations that the conceptualization “Islamic Calligraphy” carries are put forward and the practice of calligraphy in the early modern Ottoman world is approached in a broader context. The changing roles of calligraphy in social, cultural and political contexts are problematized by examining the transformations in the representation of the act of writing and the figure of calligrapher in the texts. Devhatü’l-Küttâb, the text in which the transformations in the form and content of the genre are crystallized, is analyzed within its historical context. In this analysis, the transformations realized in the bureaucratic and ulema circles, the expansion of the written culture, the actors of book culture and the changes in the field of calligraphy at the first half of the eighteenth century constitute the focus points.
Keywords: Calligraphers -- Turkey.